2005
DOI: 10.1152/ajpcell.00161.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ryanodine receptors in muscarinic receptor-mediated membrane current oscillation in urinary bladder smooth muscle

Abstract: The urinary bladder pressure during micturition consists of two components: an initial, phasic component and a subsequent, sustained component. To investigate the excitation mechanisms underlying the sustained pressure, we recorded from membranes of isolated detrusor cells from the pig, which can be used as a model for human micturition. Parasympathomimetic agents promptly evoke a large transient inward current, and subsequently during its continuous presence, oscillating inward currents of relatively small am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Taken together, the available data clearly show that muscarinic receptors in the bladder can couple to PLC activation (An et al, 2002;Kories et al, 2003;Schneider et al, 2004b;Kajioka et al, 2005) but do not support a major role for such activation in mediating bladder contraction induced by muscarinic receptor agonists. In contrast, undisputed roles exist for an influx of extracellular calcium through voltage-dependent channels (Ikeda et al, 1999;Schneider et al, 2004a,b) and for activation of a rho kinase (Peters et al, 2006) in mediating bladder contraction.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Taken together, the available data clearly show that muscarinic receptors in the bladder can couple to PLC activation (An et al, 2002;Kories et al, 2003;Schneider et al, 2004b;Kajioka et al, 2005) but do not support a major role for such activation in mediating bladder contraction induced by muscarinic receptor agonists. In contrast, undisputed roles exist for an influx of extracellular calcium through voltage-dependent channels (Ikeda et al, 1999;Schneider et al, 2004a,b) and for activation of a rho kinase (Peters et al, 2006) in mediating bladder contraction.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, undisputed roles exist for an influx of extracellular calcium through voltage-dependent channels (Ikeda et al, 1999;Schneider et al, 2004a,b) and for activation of a rho kinase (Peters et al, 2006) in mediating bladder contraction. Moreover, calcium release from intracellular stores mediated by a ryanodine receptor may also play a role (Kajioka et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures are essentially the same as previously used for detection of canonical transient receptor potential channels (Asano et al, 1999;Kajioka et al, 2005). Total RNA was isolated from pig detrusor using the RNeasy purification kit (QIAGEN, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…release and suggested that this type of Cl − channel is responsible for muscarinic receptor-induced depolarization (17).…”
Section: +mentioning
confidence: 99%